Importance of Interdisciplinary Approach to On-line Education in Technical Universities - Livshits, Irina (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the studied issue is caused by the fact that a modern educational process becomes more and more complicated. To be successful from a point of view of necessity and attractiveness for students, each new course shall include a complex of subjects that make it interdisciplinary. The results were obtained by use of a method based on formalization of course structure and contents. The purpose of the research is development of methods of online education and their formalization to ensure successful organization and operation of online courses for a wide range of technical subjects in institutions of higher education that may be also installed at international platforms such as edX [17] and others[21,22] based on usage of English as a basic language. In our research, we provide necessary contents of such a course and give an example of an online course of optic system development. Since the most up-to-date online courses are carried out in English, we recommend including teachers with good language skills and/or members of foreign universities into the educational process. Key features of a modern online education system are discussed in the work, such as availability, convenience, objectivity, etc. [18, 19, 20]. Methods of online education and development of optic systems with active usage of a foreign language have been discussed. The result of the research was growth of quality of knowledge of students studying optic system development. The project of application of the optic system development online course in a foreign language can be successfully implemented in institutions of higher technical education to teach students of the respective departments.